Management of Package C Equivalency Education for Correctional Residents at Class II.b Baturaja Detention Center - Supratman (Assyfa Journal of Islamic Studies, 2026)
As citizens, everyone has an equal right to education, including the inmates at the Baturaja Detention Center (Rutan). The Baturaja Detention Center implements the Package C equivalency program to fulfill the educational rights of inmates, while serving as an instrument for personality development. Education within a detention center presents unique management challenges and characteristics compared to regular schools. This study aims to analyze and describe the management of the Package C equivalency education program for inmates at the Class IIB Baturaja Detention Center, which includes the stages of planning, organizing, implementing, and supervising. This study employed a qualitative approach with a descriptive qualitative method. Data were collected through direct interviews with the head of the Class IIB Baturaja Detention Center, correctional officers, managers of the Annur Arba Community Learning Activity Center (PKBM) Baturaja, and participating inmates. Direct observations and documentary studies were also conducted to strengthen data validity. The results indicate that the management of the Package C program at the Baturaja Detention Center operates reasonably well through a formal partnership with an external PKBM. The initial planning stage involves assessment of inmates' interests and administrative requirements. The implementation stage faces challenges such as limited classroom space, minimal learning facilities, and scheduling adjustments to comply with detention center security protocols. The supervision stage is conducted jointly by the detention center authorities and the leadership of PKBM Annur Arba to ensure attendance and security during the learning process. In conclusion, the management of Package C education at the Baturaja Detention Center successfully provides secondary education access for inmates. However, it remains constrained by limited infrastructure and a lack of a dedicated operational budget for education within the detention center